Few-layer MoS2 saturable absorbers for short-pulse laser technology: Current status and future perspectives [Invited] - Woodward,RI; Howe,RCT; Hu,G; Torrisi,F; Zhang,M; Hasan,T; Kelleher,EJR (Photonics Research, 2015)
© 2015 Chinese Laser Press. Few-layer molybdenum disulfide (MoS2) is emerging as a promising quasi-two-dimensional material for photonics and optoelectronics, further extending the library of suitable layered nanomaterials with exceptional optical properties for use in saturable absorber devices that enable short-pulse generation in laser systems. In this work, we catalog and review the nonlinear optical properties of few-layer MoS2, summarize recent progress in processing and integration into saturable absorber devices, and comment on the current status and future perspectives of MoS2-based pulsed lasers.